(untitled) (American International Journal of Sciences and Engineering Research, 2019)
Science and technology capabilities are fundamental for social and economic progress in African countries and they are crucial components aimed at fostering growth and development of every nation as they create impact on the various sectors of governments. Maintaining and Strengthening the contributions of science and technology become more important for Africa in addressing traditional development issues and successful application of science and technology entails establishing effective institutional framework and linkages so that the various science and technology institutions and the productive sectors work in a system that is focused on achieving developmental goals without undue duplication and completion. Unfortunately, many developing countries especially the poor countries in West Africa do not have human resources, physical and economic infrastructures and access to capital to take full advantage of the science and technology expertise and achievements of the developed countries like the USA, China, and Korea etc. Conclusively, it is imperative for Africa especially West African countries to embrace science and technology as a vital tool for accelerating their socio-economic development as science and technology enhances its international competitiveness and more importantly its position in the world economy.